Встреча с домом: рассказы / Надежда Тронина - Тронина Надежда Николаевна (КнигоГрад, 2021)
Экземпляры: ф.1 (20221227) / Инвентарный номер: 63065 / Цена: / Сис.шифр: 84(2Рос.Удм)6-4 / Авт.знак: Т 73 / ГРНТИ: 17.82.32 / ББК: 84(2Рос.Удм)6-44